Diagnostic Accuracy of Contrast-Enhanced MRI in Diagnosing and Staging Urinary Bladder Carcinoma, Taking Histopathology as Gold Standard - Nisar, Piriha; Varsha, .; Sanjna, .; Shoukat, Shaista; Samad, Abdul (Biological and Clinical Sciences Research Journal, 2025)
Urinary bladder carcinoma is a common malignancy with significant morbidity and mortality. Accurate diagnosis and staging are essential for guiding treatment decisions. Contrast-enhanced magnetic resonance imaging (CE-MRI) provides a non-invasive approach for evaluating bladder tumours; however, its diagnostic accuracy compared to histopathology, the gold standard, requires validation. Objective: To evaluate the sensitivity, specificity, and diagnostic accuracy of contrast-enhanced MRI in diagnosing and staging urinary bladder carcinoma in comparison to histopathological findings. Methods: This prospective observational study was conducted at the Jinnah Postgraduate Medical Centre (JPMC), Karachi, from September 1, 2024, to February 28, 2025, following ethical approval. A total of 25 patients aged ≥18 years, of either gender, with clinical suspicion of urinary bladder carcinoma, were enrolled using non-probability consecutive sampling. Patients with contraindications to MRI or a history of contrast allergy were excluded. All patients underwent CE-MRI followed by cystoscopic biopsy for histopathological confirmation. The sensitivity, specificity, and diagnostic accuracy of CE-MRI were calculated by comparing MRI findings with histopathological results. Results: CE-MRI demonstrated a sensitivity of 53.85%, specificity of 75%, and an overall diagnostic accuracy of 64% in detecting and staging urinary bladder carcinoma. Conclusion: Contrast-enhanced MRI shows moderate diagnostic accuracy in the detection and staging of urinary bladder carcinoma. While it provides valuable non-invasive insights, its limited sensitivity underscores the continued importance of histopathology for definitive diagnosis.